The reserpine effects on the gonadotrophic cells of the male common carp Cyprinus carpio (Osteichtyes: Cyprinidae) - Lilian González-Segura; Rodolfo Cárdenas-Reygadas (Revista de Biología Tropical, 2004)
The secretion of gonadotropins (GtH) in goldfish and carp, is stimulated by GtH-releasing hormone (GnRH) and is inhibited by dopamine. Studies with antidopaminergics have demonstrated to be effective in order to stimulate the spermiation and the ovulation in different species of teleosts. The reserpine, a drug that deplets the dopamine, has shown to stimulate the spermiation in the common carp. We report here, the effects of reserpine on the number and volume of gonadotrophic cells of the common carp. Eight injections of reserpine alone, at doses of 0.5, 1.0 or 1.5 mg/ml/kg of body weight and at intervals of 48 hours, caused an increase in the number and volume of gonadotrophic cells. The dose 0.5 mg/ml/kg, presented an increase in the number and volume of gonadotrophic cells of 382% and 123%, respectively, above the control group. The dose 1.0 mg/ml/kg, showed an enhanced number and volume of gonadotrophic cells of 704% and 152%, respectively. With the dose 1.5 mg/ml/kg increase in number (171%) and volume (106%) of gonadotrophic cells was lower. The gonads of the experimental groups had an abundance of advanced states of spermatogenesis. Our results show that eight intraperitoneal injections of reserpine were responsible for an increase in gonadodrophic cell, number and volume La secreción de gonadotropinas (GtHs) en pez dorado y carpas, es estimulada por la hormona liberadora de gonadotropinas (GnRH) e inhibida por la dopamina. Trabajos previos con antidopaminérgicos demostraron ser efectivos para estimular la espermiación y ovulación, en varias especies de teleósteos. La reserpina, una sustancia que desaparece catecolaminas, se ha probado con éxito para estimular la espermiación en la carpa común. En este trabajo, reportamos los efectos de la reserpina en el número y volúmen de células gonadotropas en la carpa común. Se aplicaron ocho inyecciones de reserpina a dosis de 0.5, 1.0, y 1.5 mg/ml/kg de peso corporal, a intervalos de 48 horas entre cada inyección. Con la dosis de 0.5 mg/ml/kg, se encontró un aumento en el número de gonadotrofas de 382% y de 123% en el volumen, en comparación con los controles. La dosis de 1.0 mg/ml/kg presentó un aumento de 704% en el número de células y de 152% en el volumen celular. Con 1.5 mg/ml/kg se causó que las gonadotrofas aumentarán 171% en número y 106% en volumen. En general, las gónadas de los grupos experimentales presentaron estadios más avanzados de espermatogénesis. Nuestros resultados demuestran que ocho aplicaciones de reserpina provocan el incremento, tanto del número como del volumen, de células gonadotropas